ANALISIS MODEL 3D DATA GAYA BERAT DALAM KEGAGALAN PEMBORAN SUMUR RESERVOAR MINYAK DI AREA X - Ahmad Jahrudin; Pradityo Riyadi (Navigation Physics : Journal of Physics Education, 2020)
The exploration of oil and gas, especially in Indonesia is experiencing various challenges and varying degrees of difficulty. In this research, the researcher tries to make a 3D modeling from gravity data, where the model will show a structure to determine the central coordinates for drilling. Pertamina has carried out drilling at a location in NTT and it turns out that the well does not produce oil and gas, even though the log data reads an oil showing that the area should have the prospect of producing oil, but the wells that have been drilled do not show any oil or gas, therefore the researchers tried to make a 3D model determine the structure around the production well. In this research, it was seen that the area of the previous drilling point had deviated from the top of the up dome and it was also seen in this structure that the area was deviated by about 3 kilometers and depth must exceed 526 m, the researcher concluded that the drilling point must be at X, Y coordinates.